2021
DOI: 10.18502/tbj.v19i6.5712
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory bias in People with General Health and People Without it

Abstract: Introduction: Health is one of the categories in which it needs to look a spectrum or continuum, both physically and morally. Health is feeding good and not being sick. Many factors affect the sustain ability of health, one of the important factors is cognitive (memory) factors. Because episodic memory plays on important role in recording a person’s personal experience related to time and place. Memory bias means more or less, orientation and recall, or positive or negative and the purpose of research is to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study ndings indicate that test anxiety level was high at baseline screening. A signi cant decrease in test anxiety scores was found in post-assessment, showing that CBT effectively treated test anxiety among adolescents [79]. In addition, CBT sessions helped the participants to understand and manage their irrational fears about the outcomes of the exam.…”
Section: Discussionmentioning
confidence: 91%
“…The study ndings indicate that test anxiety level was high at baseline screening. A signi cant decrease in test anxiety scores was found in post-assessment, showing that CBT effectively treated test anxiety among adolescents [79]. In addition, CBT sessions helped the participants to understand and manage their irrational fears about the outcomes of the exam.…”
Section: Discussionmentioning
confidence: 91%
“…1 The simulation source code, input files, and example structures are archived on GitHub. 58 Table I gives the particle properties for the simulations here, based on the CPG-A12 anode used in the previous study. The simulated dry weight composition is 92% CPG-A12 active material, 6% polyvinylidene fluoride (PVDF), and 2% carbon black.…”
Section: Electrode Materials and Their Morphological Propertiesmentioning
confidence: 99%
“…(14) Many studies have shown positive and useful effects of antenatal preparation, in Iran a study conducted by Firouzbakht, M. et al, disclosed that Prenatal child birth education and psychological support of mothers during labor can reduce anxiety, pain intensity, and interventions such as episiotomy and cesarean section . (15 ) Other study conducted by Siraj et.al, in Jeddah at Saudi Arabia, it was a quantitative, randomized controlled trial, aimed to assess the effectiveness of lower back massage on reducing labor pain for primiparous. This study revealed that a lower back massage is sig nificantly an effective, non-Pharmacological and alternative intervention, to reduce labor pain and increase the level of mothers' satisfaction .…”
Section: Introductionmentioning
confidence: 99%